Polyunsaturated fatty acids and the risk of multiple sclerosis - Bjørnevik, Kjetil; Chitnis, Tanuja; Ascherio, Alberto; Munger, Kassandra L (Multiple sclerosis, 2017)
Results from previous studies on polyunsaturated fatty acid (PUFA) intake and multiple sclerosis (MS) risk are conflicting. To prospectively investigate the association between dietary intake of PUFA and MS risk. We followed 80,920 women from Nurses' Health Study (1984-2004) and 94,511 women from Nurses' Health Study II (1991-2009) who reported on diet using a validated food frequency questionnaire every 4 years and identified 479 incident MS cases during follow-up. We used Cox regression to estimate hazard ratios (HRs) and 95% confidence intervals (CIs), for the effect of PUFA intake on MS risk adjusting for age, latitude of residence at age 15, ancestry, cigarette smoking, supplemental vitamin D intake, body mass index, and total energy intake. Higher intake of total PUFA at baseline was associated with a lower risk of MS (HR top vs bottom quintile: 0.67, 95% CI: 0.49-0.90, p trend = 0.01). Among the specific types of PUFA, only α-linolenic acid (ALA) was inversely associated with MS risk (HR top vs bottom quintile: 0.61, 95% CI: 0.45-0.83, p trend = 0.001). The long-chain fatty acids eicosapentaenoic acid (EPA) and docosahexaenoic acid (DHA) were not associated with MS risk. Low dietary PUFA intake may be another modifiable risk factor for MS.